Suppression of kinesin expression in cultured hippocampal neurons using antisense oligonucleotides (The Rockefeller University Press, 1992)
Kinesin, a microtubule-based force-generating molecule, is thought to translocate organelles along microtubules. To examine the function of kinesin in neurons, we sought to suppress kinesin heavy chain (KHC) expression in cultured hippocampal neurons using antisense oligonucleotides and study the phenotype of these KHC "null" cells. Two different antisense oligonucleotides complementary to the KHC sequence reduced the protein levels of the heavy chain by greater than 95% within 24 h after application and produced identical phenotypes. After inhibition of KHC expression for 24 or 48 h, neurons extended an array of neurites often with one neurite longer than the others; however, the length of all these neurites was significantly reduced. Inhibition of KHC expression also altered the distribution of GAP-43 and synapsin I, two proteins thought to be transported in association with membranous organelles. These proteins, which are normally localized at the tips of growing neurites, were confined to the cell body in antisense-treated cells. Treatment of the cells with the corresponding sense oligonucleotides affected neither the distribution of GAP-43 and synapsin I, nor the length of neurites. A full recovery of neurite length occurred after removal of the antisense oligonucleotides from the medium. These data indicate that KHC plays a role in the anterograde translocation of vesicles containing GAP-43 and synapsin I. A deficiency in vesicle delivery may also explain the inhibition of neurite outgrowth. Despite the inhibition of KHC and the failure of GAP- 43 and synapsin I to move out of the cell body, hippocampal neurons can extend processes and acquire as asymmetric morphology.